The Effect of Power Plants on Local Housing Values and Rents - Davis, Lucas W. (The Review of Economics and Statistics, 2011)
This paper uses restricted census microdata to examine housing values and rents for neighborhoods in the United States where power plants were opened during the 1990s. Compared to neighborhoods with similar housing and demographic characteristics, neighborhoods within 2 miles of plants experienced 3%–7% decreases in housing values and rents, with some evidence of larger decreases within 1 mile and for large-capacity plants. In addition, there is evidence of taste-based sorting, with neighborhoods near plants associated with modest but statistically significant decreases in mean household income, educational attainment, and the proportion owner-occupied.